20 Years of fish immunotoxicology – what we know and where we are. (3rd July 2017) - Rehberger, Kristina; Werner, Inge; Hitzfeld, Bettina; Segner, Helmut; Baumann, Lisa
Abstract: Despite frequent field observations of impaired immune response and increased disease incidence in contaminant-exposed wildlife populations, immunotoxic effects are rarely considered in ecotoxicological risk assessment. The aim of this study was to review the literature on immunotoxic effects of chemicals in fish to quantitatively evaluate (i) which experimental approaches were used to assess immunotoxic effects, (ii) whether immune markers exist to screen for potential immunotoxic activities of chemicals, and (iii) how predictive those parameters are for adverse alterations of fish immunocompetence and disease resistance. A total of 241 publications on fish immunotoxicity were quantitatively analyzed. The main conclusions included: (i) To date, fish immunotoxicology focused mainly on innate immune responses and immunosuppressive effects. (ii) In numerous studies, the experimental conditions are poorly documented, as for instance age or sex of the fish or the rationale for the selected exposure conditions is often missing. (iii) Although a broad variety of parameters were used to assess immunotoxicity, the rationale for the choice of measured parameters was often not given, remaining unclear how they link to the suspected immunotoxic mode of action of the chemicals. (iv) At the current state of knowledge, it is impossible to identify a set of immune parameters that could reliably screen for immunotoxic potentials of chemicals. (v) Similarly, in fish immunotoxicology there is insufficient understanding of how and when chemical-induced modulations of molecular/cellular immune changes relate to adverse alterations of fish immunocompetence, although this would be crucial to include immunotoxicity in ecotoxicological risk assessment.